Hydrostatics and Stability of Marine Vehicles Theory and Practice - Lee, Byung Suk.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses the hydrostatics and stability of ships and other floating marine structures - a fundamental aspect of naval architecture and offshore engineering for naval architects and marine engineers. It starts from the most basic concepts, assuming that the reader has no prior knowledge of the subject. By presenting the topic in a methodical and step-by-step manner, the book helps students to enhance their understanding, while also providing valuable guidelines for lecturers teaching related courses. .
Basic Ship Geometry -- Basic Hydrostatics -- Moments and Centroids -- Numerical Integration Methods -- Trim and Longitudinal Stability -- Statical Stability at Small Heels Angles -- Statical Stability at Large Heel Angles -- Dynamical Stability -- Intact Stability Criteria -- Damage Stability and Watertight Subdivision. .
Keywords: Offshore structures; Continuum mechanics; Mechanics, Applied; Solids; Fluid mechanics; Engineering design; Offshore Engineering; Continuum Mechanics; Solid Mechanics; Engineering Fluid Dynamics; Engineering Design